Hash algorithm comparison through a PIC32 microcontroller - Asmae Zniti; Nabih El Ouazzani (Institute of Advanced Engineering and Science, 2023)
This paper presents a comparative study involving SHA-3 final round candidates along with recent versions of hash algorithms. The proposed comparison between hash functions is performed with respect to cycles per byte and memory space. Tests are also carried out on a PIC32-based application taking into account several input cases, thus resulting in a set of ranked algorithms in terms of their specified metrics. The outcome of this work represents a considerable contribution in data protection and information security in relation to various communication and transmission systems, serving as a handy reference for developers to select an appropriate hash algorithm for their particular use condition.